Peningkatan Kemampuan Guru dalam Menyusun Soal Penilaian Harian menggunakan Metode Pendampingan Teamwork Pola Corona - Mahmudah, Siti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to help improve teachers' ability to compile daily assessment questions at SD Negeri Surodadi II Ponjong through corona pattern teamwork mentoring activities. This study used the School Action Research (PTS) design. The subjects of the study were 6 class teachers and 2 subject teachers of SDN Surodadi II Ponjong. Data collection through observation of teacher participation in mentoring and assessment of action results in the form of teachers' ability to compile daily assessment questions using an assessment format. While data analysis is used with qualitative descriptive analysis. The results showed an increase in the teacher's ability to compile daily assessment questions marked by an average score at the end of the second cycle of 82.55, of the scores obtained by the teacher as many as 87.5% achieved scores in the minimum good category.